Melody - Andrews, V. C. (New York A Pocket Star Book, 1996)
Grieving over her beloved father's death, talented violinist Melody Logan is astonished when her depressive mother takes them to live at the Logan estate, where she learns a devastating secret about her parents.
Keywords: Violinists -- Psychological fiction -- Families -- Young women